A Review on the Drug Delivery System - Singh, Abhishek; Pal, Niketa; Sharma, Rishikesh; Saini, Aryendu Kumar (Asian Journal of Pharmaceutical Research and Development, 2021)
Drug administration is the mechanism or procedure by which a medicinal substance is delivered to produce a beneficial result in humans or animals. Nasal and pulmonary drug delivery pathways are gaining growing significance for the treatment of human illnesses. Such routes provide promising alternatives to the delivery of parenteral drugs particularly for peptide and protein therapies. Many drug delivery devices have been developed for this purpose, and are being tested for nasal and pulmonary delivery. These contain amongst others liposomes, proliposomes, microspheres, gels, prodrugs, cyclodextrins. Nanoparticles made up of biodegradable polymers show confidence that they meet the stringent criteria imposed on such delivery systems, such as the ability to be transferred to an aerosol, stability against forces produced during aerosolisation, biocompatibility, targeting of particular sites or cell populations in the lungs, predetermined release of the drug and degradation within the lungs.